2018
DOI: 10.1002/cbdv.201800374
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Composition, Antioxidant Potential and Cholinesterase Inhibition Potential of Extracts from Mentha pulegium L.

Abstract: The aim of this work was to perform the phytochemical analysis as well as antioxidant and anticholinesterase potential of hot water and methanolic extracts from Mentha pulegium L., Lamiaceae, wild growing in Bosnia and Herzegovina. It is a plant that is traditionally used in Bosnia and Herzegovina medicine to treat gastrointestinal and neurological disorders. By HPLC‐DAD analysis of tested extracts, 15 phenol compounds were identified and quantified. Rosmarinic acid was the most abundant compound in both extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 39 publications
(45 reference statements)
1
17
0
Order By: Relevance
“…El-Tarf [35] Tunisia [43] Croatia [15] Turkey [ The amount of extracted phenolics depends on some parameters, including the extraction temperature, time, pH, and solvent polarity [57,58]. The results of other authors may vary moderately from ours due to these factors.…”
Section: Plant Current Study Previous Studiesmentioning
confidence: 80%
See 1 more Smart Citation
“…El-Tarf [35] Tunisia [43] Croatia [15] Turkey [ The amount of extracted phenolics depends on some parameters, including the extraction temperature, time, pH, and solvent polarity [57,58]. The results of other authors may vary moderately from ours due to these factors.…”
Section: Plant Current Study Previous Studiesmentioning
confidence: 80%
“…There are many studies focusing on the biological and pharmacological studies of plants (aerial and underground parts) in folk medicine [ 13 , 14 , 15 ]. Several studies on medicinal plants have reported that there are marked differences in chemical composition (total flavonoid, total phenolic contents), mineral count, and biological activity due to differences in geographical regions and locations across the world.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have documented the antioxidant activity of Mentha pulegium extracts and the essential oils originating from Mentha pulegium . 42 As AgNPs would be coating by the bioactive constituent involved in the Mentha pulegium leaf extract, the AgNPs biosynthesized using Mentha pulegium leaf extract are anticipated to exhibit powerful antioxidant activity. Thus, we performed the DPPH experiment to evaluate the antioxidant activity of biosynthesized AgNPs, where the DPPH method is considered as one of the quickest methods.…”
Section: Resultsmentioning
confidence: 99%
“…All these chemical constituents contribute to multidirectional pharmacological activities. Some of the remarkable bioactivities reported within this plant family are anti-allergic (Malik et al, 2003; Makino et al, 2003; Kim et al, 2009), anti-inflammatory (Borges et al, 2018), antimicrobial (Khoury et al, 2016; Cocan et al, 2018), free radical scavenging (Khaled-Khodja et al, 2014; Politeo et al, 2018), antinociceptive (Hwang et al, 2018; Uritu et al, 2018), anti-cancer activities (Nguyen et al, 2018; Sajjadi et al, 2018), etc. Many pharmacological activities of the Lamiaceae family have been widely studied and investigated.…”
Section: Anti-allergic Activitymentioning
confidence: 99%